2016
DOI: 10.1371/journal.pone.0148904
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Calcium Amount in a New Experimental Model: A Comparison between Ultrasound and Computed Tomography

Abstract: PurposeCalcification is an important prognostic factor in aortic valve stenosis. However, there is no ultrasound (US) method available to accurately quantify calcification in this setting to date. We aimed to validate a new US method for measuring the amount of calcium in an in vitro model, and compare it to computed tomography (CT), the current imaging gold standard.Materials and MethodsAn agar phantom (2% agar) was made, containing 9 different amounts of calcium-hydroxyapatite Ca5(PO4)3OH (2 to 50mg). The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…The histological analyses showed a fragmentation of calcifications with the preservation of the leaflet superficial structures. Micro-CT imaging, which can be considered as a gold standard for the valvular calcification evaluation15,16, confirmed that micro-fragmentations appeared inside the calcification after PCU. This micro-fragmentation of large calcifications could explain the overall change of biomechanical properties which leads to the improvement of the leaflet motion.…”
Section: Discussionmentioning
confidence: 87%
“…The histological analyses showed a fragmentation of calcifications with the preservation of the leaflet superficial structures. Micro-CT imaging, which can be considered as a gold standard for the valvular calcification evaluation15,16, confirmed that micro-fragmentations appeared inside the calcification after PCU. This micro-fragmentation of large calcifications could explain the overall change of biomechanical properties which leads to the improvement of the leaflet motion.…”
Section: Discussionmentioning
confidence: 87%